Organisationsdefizite der deutschen Gewerkschaften - Hendrik Biebeler; Hagen Lesch (Wirtschaftsdienst, 2015)
Eine Auswertung der Allgemeinen Bevölkerungsumfrage der Sozialwissenschaften (ALLBUS) ergibt, dass der Organisationsgrad der Gewerkschaften unter den Arbeitnehmern im Jahr 2014 nur noch bei knapp 18% lag. Damit wurde im wiedervereinigten Deutschland ein neuer Tiefstand erreicht. Rekrutierungsdefizite bestehen vor allem bei Frauen, bei Jüngeren und in Ostdeutschland. Außerdem sind Angestellte in den Gewerkschaften ebenso unterrepräsentiert wie Hochqualifizierte. – – The results of the recently released German General Social Survey (ALLBUS) show that in 2014 the net density rate of trade unions in Germany declined to less than 18 per cent. This was the lowest level since German unification. An in-depth analysis of union membership reveals that unionisation of male, full-time and older employees is above average. The latest membership decline will continue if the unions do not succeed in organising more women, young people and white collar workers. Furthermore, unions have not yet been able to profit from scepticism towards liberal economic policies, which has slightly grown within the group of employees since 2004, as the index of economic freedom reveals.
Keywords: J51; J52; J53; 330; Gewerkschaftsmitgliedschaft; Deutschland